Effect of Nano-CuO grain size on heat transfer performance of copper substrate - Mahmood, M. H.; Maleque, Md. Abdul; -, Suryanto (The Mattingley Publishing Co., Inc., 2020)
This paper presents the experimental results of nano copper oxide coating on the heat transfer performance of the copper substrate. The thermal effect of Nano copper oxide coating investigated by using an experimental thermal system consisted of three sections: evaporator, adiabatic, and condenser. The copper oxide (CuO) coating performed for the inner surface of copper pipe using an electrochemical oxidation method in an oxalic acid bath with applying a voltage of 5 volts at ambient temperature. The experimental tests performed for coated and uncoated copper pipes. The effects of CuO grain size on specific surface area (SSA) and material characteristics feature are investigated. Characterization of the CuO coat-ing were conducted using X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM). The aver-age grain size of the oxide coating was ~44 nm, with an average coating thickness of ~11 micrometers. The CuO coated substrate showed lower thermal resistance property compared to uncoated substrate. However, the SSA of the coated substrate in decreased with the increasing of CuO grain size. Results show that the Nano-copper oxide coating enhances the heat transfer performance of the copper pipe, as a result of the increase in the specific surface area of Nano range grain size CuO by reducing the thermal resistance, and increasing the thermal conductivity. This result opens a new avenue to overcome the industrial challenge in the development of the heat exchangers design with Nano-coating with increased heat transfer efficiency and reduced size of the heat transfer equipment.